Noise Reducing in Speech Signals Using Wavelet Technology - Romanyshyn, Y.; Tkachenko, V. (ХНУРЭ, 2011)
In this paper the features of reducing of background noise in speech signals using discrete wavelet transforms with different wavelet bases, the analysis of choosing of different wavelet bases and decomposition levels of the signal are considered.
Keywords: wavelet bases; noise; discrete wavelet transform; speech signal